2022
DOI: 10.7554/elife.77419
|View full text |Cite
|
Sign up to set email alerts
|

EZ Clear for simple, rapid, and robust mouse whole organ clearing

Abstract: Tissue clearing for whole organ cell profiling has revolutionized biology and imaging for exploration of organs in three-dimensional space without compromising tissue architecture. But complicated, laborious procedures, or expensive equipment, as well as the use of hazardous, organic solvents prevent the widespread adoption of these methods. Here, we report a simple and rapid tissue clearing method, EZ Clear, that can clear whole adult mouse organs in 48 hr in just three simple steps. Samples stay at room temp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Furthermore, we conducted simultaneous staining of hypoxia and blood vessels in the kidney. It has been reported that major renal blood vessels and partial glomerular capillaries can be labeled with Evans blue. , We prepared a kidney sample in which blood vessels were labeled with Evans blue and in which hypoxic regions were labeled with Pimo-BODIPY. By fluorescence imaging with LSFM, we succeeded in the simultaneous 3D visualization of renal hypoxia (green in Figure E) and blood vessels (red in Figure E) (Movie 2).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we conducted simultaneous staining of hypoxia and blood vessels in the kidney. It has been reported that major renal blood vessels and partial glomerular capillaries can be labeled with Evans blue. , We prepared a kidney sample in which blood vessels were labeled with Evans blue and in which hypoxic regions were labeled with Pimo-BODIPY. By fluorescence imaging with LSFM, we succeeded in the simultaneous 3D visualization of renal hypoxia (green in Figure E) and blood vessels (red in Figure E) (Movie 2).…”
Section: Resultsmentioning
confidence: 99%
“…After washing, Cy3 or Alexa Fluor 647-conjugated cross-adsorbed polyclonal secondary antibodies targeting rat, rabbit, goat and/or mouse IgG (Jackson Immunoresearch Cat# 712-165-153, Cat# 711-165-152, Cat# 705-605-147 and/or Cat# 115-605-206) were incubated with sections at 1:500 in PBS + 0.3% triton X-100 overnight. After additional washes, sections were either mounted in Vectashield (Vector Laboratories Cat# H-1700) for standard confocal imaging on a Nikon A1r microscope, or cleared after staining using the EZ clear protocol (47) for 3D imaging with a Nikon AZ100M confocal microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Lungs were fixed overnight at 4oC with gentle agitation. Lungs were then cleared using the EZclear protocol( 44 ). Briefly, the next morning, lungs were washed 4x 30 minutes each in PBS then incubated with 50% (v/v) THF (Sigma-Aldrich) in sterile milli-q water for 16 hours.…”
Section: Methodsmentioning
confidence: 99%